KAJIAN CITRA KOTA SEBAGAI BRANDING KAWASAN CAGAR BUDAYA KOTA TEGAL DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN - Suci Aini Suryaning Pertiwi; Shita Paramuditaningtyas (Vastutara : Arsitektur, Digital, Sejarah, Struktur dan Lingkungan, 2025)
The development of a city can affect acculturation and agglomeration. A city that has characteristics as its own identity related to the city's image. According to Kevin Lynch's Theory, there are five elements that form a city's image, including landmarks, paths, districts, nodes, and edges. Based on the Tegal City Regional Regulation in the Regional Spatial Plan and the Tegal Mayor's Regulation in the Detailed Spatial Plan, it is stated that there are historical buildings, one of which is the cultural heritage area of ​​West Tegal District with quite massive urban activities. However, the West Tegal cultural heritage area is starting to lose its identity, as seen from the destroyed buildings that are not in harmony with their original structure and form. So the purpose of this study is to examine the elements of city image to carry out branding of the Tegal City Cultural Heritage Area in supporting sustainable development. The preparation of the article uses a qualitative descriptive method by relying on information from literature and observation. The results of the study show that there are three components that influence the image of the area, including identity as a potential for tourism development; the existence of a spatial structure; and meaning as a perceived potential. Recommendations in conservation conservation areas are to improve public facility systems such as drainage and green open spaces, encourage community participation to become part of local conservation, and make cultural heritage areas part of city life through culture-based tourism.